2014
DOI: 10.1017/s071498081400018x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Community-Engaged Arts Program on Older Adults’ Well-being

Abstract: This mixed-methods study evaluated the effect of a community-engaged arts program on the physical, emotional, and social well-being of seniors. Weekly workshops were offered over a three-year period at community centers where artists worked with four groups of seniors to produce a collective art piece or performance for public presentation. Participants completed pre- and post- questionnaires, and group interviews were conducted at the program's end. Paired t-test analyses indicated that seniors experienced im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 23 publications
2
48
0
1
Order By: Relevance
“…We identified 272 systematic reviews. Eight met inclusion criteria, and we selected the four 5,[31][32][33] most recent systematic reviews, which were published in 2018. We evaluated the 131 unique primary studies contained in these systematic reviews as well as 1,572 primary studies from a search from the past 2 years.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 272 systematic reviews. Eight met inclusion criteria, and we selected the four 5,[31][32][33] most recent systematic reviews, which were published in 2018. We evaluated the 131 unique primary studies contained in these systematic reviews as well as 1,572 primary studies from a search from the past 2 years.…”
Section: Resultsmentioning
confidence: 99%
“…every 2 weeks). Most interventions lasted between 3 and 12 weeks, with a few lasting for extended periods (26 weeks [ 73 ], 30 weeks [ 66 ] and 3 years [ 96 ]). In one study, the intervention duration was not clear [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 12 studies were rated as high and medium-high RoB [ 65 , 69 , 70 , 72 – 74 , 76 , 78 , 85 , 95 , 103 , 104 ], 12 studies as moderate RoB [ 70 , 71 , 75 , 80 , 83 , 84 , 93 , 94 , 97 , 98 , 100 , 102 ] and 21 as low or low-moderate RoB [ 66 68 , 77 , 79 , 81 , 82 , 86 , 87 , 89 , 90 , 92 , 96 , 98 100 , 105 – 107 ]. The main RoB issues with these studies included small sample size, poor selection of participants and differences observed between intervention and control group participants at baseline.…”
Section: Resultsmentioning
confidence: 99%
“…Perry and co-workers [ 24 ], emphasised the need to create workplaces where working practices promote nurses’ health and well-being, or at least are configured to minimise deleterious effects of work related stress on health. Arts activities are important in educational programmes for nursing and other health care professionals [ 25 , 26 , 27 , 28 ] with growing evidence that arts activity has a positive impact on people‘s health and well-being [ 29 , 30 , 31 , 32 ]. Art activities could be used as a tool to improve well-being at work [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%